Conceptualising luxury residential property for marketing - Amy Chuon; Hasniyati Hamzah; Abdul Ghani Sarip (Penerbit Universiti Kebangsaan Malaysia, 2017)
Today, the luxury residential property segment in Malaysia has experienced product development in an exponential rate, causing the segment to encompass more than just exclusivity, fancy address and facilities. For purchasers, the luxury concept has moved beyond the physical product. As such, it is important for marketers to understand how luxury is perceived from a larger perspective so that they can gauge, shape and fulfil potential purchasers’ expectations. In the current soft market for luxury apartments, such understanding is crucial to the business sustainability of developers. This paper attempts to conceptualise luxury residential property based on an extensive review of the relevant literature. Ultimately, the findings of this paper will contribute towards an effective marketing strategy to boost the sale of luxury high-rise residential properties which are currently experiencing a soft market. The 4P’s of marketing underpinned the formulation of the concept of luxury residential spaces in this paper. Information is gleaned from texts, articles, journals, books and seminar papers from various perspectives including real estate, marketing, economics and sociology mainly from international authors. As such, the scope of this paper is much wider than simply capturing the nuances of local culture in shaping the notion of luxury residences, but rather take a global and academic view of the conceptualisation of luxury residential property. The framework of luxury residential property as presented in this paper will give practitioners and researchers an informed insight into the evolution, normalisation and development of the concepts of luxury and luxury residence with potential applications for benchmarking and research. Although far from definitive, sufficient theories, definitions and discourse from the body of knowledge on luxury real estate have been covered and thus provide a valuable reference.